Exchange rate volatility and international trade: The option approach - Günter Franke (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1986)
Usually it is argued that an increase in exchange rate volatility reduces the volume of international trade since trading firms are risk averse. This paper shows for risk neutral firms that the expected international trade volume in standardized commodities grows with exchange rate volatility. The firms adjust their trade volume to the exchange rate level. The more favorable the exchange rate is, the higher is the export volume. If the rate drops below some level, exports are stopped. Thus international trading represents an option for firms. Its value increases with exchange rate volatility.
Keywords: 330; Währungsmanagement; Wechselkurs; Internationale Betriebswirtschaftslehre